Art: The Grand Illusion - Stoehr, Alexander (East Carolina University, 2019)
My presentation facilitates an understanding of everyday design choices and the potential influence it has on a viewer. From marketing designs to popular film I do my best to breakdown my understanding of the artist/audience relationship. I then attempt to provide examples of this potential influence. But whether this power is good, bad, or neutral, however, is up to my audience. I will carry this thought process with me through my career.
Keywords: Visual Art; Suspension of Disbelief; Artist and Audience